ROLE OF WAVE GROUPS IN RESUSPENSION OF SANDY SEDIMENTS - Williams J.J.; Rose C.P.; Thorne P.D. (My University, 2002)
Field measurements of the resuspension of medium/coarse sand by orthogonal wave-currents in approximately 20 m water depth are presented and discussed. Velocity squared-suspended sediment cospectra indicate resuspension events occur at incident wave frequencies O(12 s) and at lower frequencies O(60 s) corresponding approximately to wave groups. Wave run-length parameters, determined for six wave records, are used to quantify bottom sediment response to wave group forcing. Results show that under groups of more than five waves, average suspended sediment concentration values, C, are approximately three times larger than values measured beneath a single wave of comparable height. Analyses demonstrate that the apparent in situ grain settling velocity also increases under groups of waves. A simple empirical expression, which quantifies the wave group influence on the near-bed 'reference' suspended sediment concentration, is presented.
Keywords: WAVE GROUP; ENHANCED SEDIMENT CONCENTRATION; SEDIMENT RESUSPENSION